2019
DOI: 10.1200/jgo.18.00225
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Cohorts to Generate the Evidence Base to Reduce the Burden of Breast Cancer in Sub-Saharan Africa: Results From a Feasibility Study in Kenya

Abstract: PURPOSE By 2025, Kenya is estimated to experience a two-thirds increase in the incidence of breast cancer. Local research is necessary to generate evidence to inform policy, public health, and medical practice. There have been no longitudinal cohort studies in sub-Saharan Africa of women with and without breast cancer. Our aim is to assess the feasibility of conducting cohort studies in Kenya that consider clinical characteristics, socioeconomic factors, and self-care behaviors. METHODS We initiated a short-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Knowledge of symptoms and signs based on recall methods, like in our case, is generally lower than in studies that use recognition methods . Studies in Kenya using recognition methods have revealed good knowledge of other symptoms .…”
Section: Discussionmentioning
confidence: 52%
“…Knowledge of symptoms and signs based on recall methods, like in our case, is generally lower than in studies that use recognition methods . Studies in Kenya using recognition methods have revealed good knowledge of other symptoms .…”
Section: Discussionmentioning
confidence: 52%